Variações genéticas e as suas possíveis associações com as respostas inflamatórias em jogadores de futebol - Tane Kanope Ferreira Serpa (2022)
Football is a sport characterized by high-intensity intermittent actions, which demand great eccentric force generation, which in turn, result in increased inflammatory response after training and matches. Genetic factors have been shown to have a great influence not only on components of athletic performance, but also on activation and resolution of inflammation, muscle tissue regeneration, and other phenotypes. Thus, the objective of the present study was to investigate the association of genetic factors with inflammation-related phenotypes in football players after a training session with a predominance of eccentric actions. The sample was composed of 47 male football athletes from the under-20 category who belong to clubs from the first division of Brazilian football. Blood samples were collected in the moments Pre, 3, 24 and 48 hours after the training session to evaluate inflammatory responses (hematological analyses (hemogram), creatine phosphokinase (CK), high sensitivity quantitative C-reactive protein (CRP), tumor necrosis factor (TNFα), interleukin 6 (IL-6) and insulin-like growth factor type 1 (IGF-1)). In study 1, it was observed that individuals with the XX genotype for the ACTN3 rs1815739 polymorphism (SNP), exhibit greater inflammatory responses (Neutrophils, Monocytes and TNFα (p<0.01)), possible delayed IL-6 signaling, and lower IGF-1 concentrations compared to athletes carrying the R allele (p<0.01). The results of study 2, suggest that the genetic distance approach based on 10 polymorphisms (SNPs) and performance related Fst compared to 1000genomes were replicable in similar but independent populations of football players. In a broader context from a genetic point of view, in study 3, the association of several polymorphisms (analyzed individually and together) and the inflammatory responses of athletes was verified. Of the 28 SNPs analyzed, 9 (ACTN3 rs1815739, COL5A1 rs12722, COL5A1 rs3196378, HGF rs5745697, IGF1 rs35767, IL-6 rs1800795, MMP3 rs679620, SLC30A8 rs13266634, SOX15 rs4227) were individually associated with biomarkers and 7 SNPs (COL5A1 rs12722, COL5A1 rs3196378, COL5A1 rs1800012, HGF rs5745697, IGF1 rs35767, IL-6 rs1800795 and MMP3 rs679620) analyzed in combination explained between 16% and 40% of the variation in inflammatory responses in football players. From the results presented, it can be concluded that the genotype profile can be considered for a more individualized training load distribution as well as in the elaboration of recovery strategies for high level athletes between training sessions and games of high physical and physiological demand.